Ciência cidadã e comunicação pública: Alternativas educacionais para o ensino médio na área de resíduos sólidos urbanos - Martins, Diny Gabrielly de Miranda (2022)
This study analyzes how the principles and foundations of citizen science can contribute to the engagement of high school students and teachers in the municipality of Formiga in the implementation of urban solid waste projects. As specific objectives, it was intended: a) to identify the knowledge of students and teachers in the 3rd year of high school at Rodolfo Almeida State School, about science, citizen science and urban solid waste; b) systematize the knowledge of students and teachers about citizen science and solid waste to support the implementation of an educational project in the area of solid waste; c) prepare a didactic-pedagogical proposal based on the principles of citizen science to support the performance of teachers and voluntary participation of students in the area of solid urban waste, in the city of Formiga-MG. It is an exploratory and descriptive research, as it analyzes the theme of citizen science that is still little explored and studies in this area are incipient. It has a qualitative and quantitative approach. The study was carried out with 36 students and 12 teachers from the third-year high school class at Escola Rodolfo Almeida, in Formiga-MG. To identify the participants' knowledge about science, citizen science and solid waste, questionnaires were applied. To collect qualitative data, an interview was carried out with three students in the class. The content analysis technique was used to analyze the collected data. The results indicate that most participants have a limited understanding of science and are unaware of the practices and principles of citizen science and how the lay public can collaborate in scientific research. However, they recognize that the role of non-scientists in scientific projects is essential for the dissemination of knowledge and the development of society. Thus, the instruments of public communication of science are relevant to broaden the view on science and citizen science, since it allows the common citizen to appropriate knowledge in different areas of knowledge. The results make evident the need to raise the awareness of the ant population about the problem of waste production and garbage disposal. As a result of the research, a didactic proposal was produced for teachers to use when dealing with the issue of solid waste, allowing students to act as volunteers in a scientific project.